Clinical and pathologic features of familial pancreatic cancer - Jeremy L. Humphris; Amber L. Johns; Skye H. Simpson; Mark J. Cowley; Marina Pajic; David K. Chang; Adnan Nagrial; Venessa Chin; Lorraine A. Chantrill; Mark Pinese; R. Scott Mead; Anthony J. Gill; et al. (2014)
BACKGROUND Inherited predisposition to pancreatic cancer contributes significantly to its incidence and presents an opportunity for the development of early detection strategies. The genetic basis of predisposition remains unexplained in a high proportion of patients with familial PC (FPC). METHODS Clinicopathologic features were assessed in a cohort of 766 patients who had been diagnosed with pancreatic ductal adenocarcinoma (PC). Patients were classified with FPC if they had ≥1 affected first‐degree relatives; otherwise, they were classified with sporadic PC (SPC). RESULTS The prevalence of FPC in this cohort was 8.9%. In FPC families with an affected parent‐child pair, 71% in the subsequent generation were 12.3 years younger at diagnosis. Patients with FPC had more first‐degree relatives who had an extrapancreatic malignancy (EPM) (42.6% vs 21.2; P <.0001), particularly melanoma and endometrial cancer, but not a personal history of EPM. Patients with SPC were more likely to be active smokers, have higher cumulative tobacco exposure, and have fewer multifocal precursor lesions, but these were not associated with differences in survival. Long‐standing diabetes mellitus (>2 years) was associated with poor survival in both groups. CONCLUSIONS FPC represents 9% of PC, and the risk of malignancy in kindred does not appear to be confined to the pancreas. Patients with FPC have more precursor lesions and include fewer active smokers, but other clinicopathologic factors and outcome are similar to those in patients with SPC. Furthermore, some FPC kindreds may exhibit anticipation. A better understanding of the clinical features of PC will facilitate efforts to uncover novel susceptibility genes and the development of early detection strategies. Cancer 2014;120:3669–3675. © 2014 American Cancer Society .